TGF-β as Multifaceted Orchestrator in HCC Progression: Signaling, EMT, Immune Microenvironment, and Novel Therapeutic Perspectives - Dituri, Francesco; Mancarella, Serena; Cigliano, Antonio; Chieti, Annarita; Giannelli, Gianluigi (Seminars in Liver Disease, 2019)
Therapeutic attempts to treat hepatocellular carcinoma (HCC) frequently result in a poor response or treatment failure. The efficacy of approved drugs and survival expectancies is affected by an ample degree of variability that can be explained at least in part by the enormous between-patient cellular and molecular heterogeneity of this neoplasm. Transforming growth factor-β (TGF-β) is hyperactivated in a large fraction of HCCs, where it influences complex interactive networks covering multiple cell types and a plethora of other local soluble ligands, ultimately establishing several malignancy traits. This cytokine boosts the invasiveness of cancerous epithelial cells through promoting the epithelial-to-mesenchymal transition program, but also skews the phenotype of immune cells toward a tumor-supporting status. Here, we discuss recent strategies pursued to offset TGF-β-dependent processes that promote metastatic progression and immune surveillance escape in solid cancers, including HCC. Moreover, we report findings indicating that TGF-β reduces the expression of the proinflammatory factors CCL4 and interleukin-1β (IL-1β in human ex vivo treated HCC tissues. While this is consistent with the anti-inflammatory properties of TGF-β, whether it is an outright tumor promoter or suppressor is still a matter of some debate. Indeed, IL-1β has also been shown to support angiogenesis and cell invasiveness in some cancers. In addition, we describe an inhibitory effect of TGF-β on the secretion of CCL2 and CXCL1 by HCC-derived fibroblasts, which suggests the existence of an indirect stroma-mediated functional link between TGF-β and downstream immunity.
Keywords: transforming growth factor-β; HCC; galunisertib; cytokine; immunity